Workshop Pengayaan Materi Dan Pelatihan Penyelesaian Soal-Soal Olimpiade IPA Bagi Guru MIM Tegalampel, Klaten - Hidayat, Muhamad Taufik; Faiziyah, Nuqthy; Setiyoso, Hendiawan; Cahyuningsih, Windy; Anarani, Dewi; Novandi, Rizki Yakaria (University of Islam Malang, 2020)
MIM Tegalampel is one of primary school in Klaten Regency which is pioneering the special program of the Science Olympiad (OSN). The purpose of this community service program is to provide knowledge and skills to teachers of MIM Tegalampel so they can identify the types of OSN material, apply several mastery strategies for OSN material, as well as solve OSN problems quickly and accurately. The method used is the method of enrichment, demonstration and try out. The evaluation of the implementation of this community service consisted of an initial evaluation in the form of a pre-test, the final evaluation in the form of a post-test, as well as an evaluation of the implementation. Based on the result of the workshop for teachers of MIM Tegalampel, it can be concluded that in general the participants considered the workshop scheduling to be appropriate, time sharing was appropriate, the balance between theory and practice was also appropriate. Participants considered most of the expectations and objectives of the workshop had been fulfilled. The evaluation result showed that participants had increased skills in identifying the types of OSN material. There was also an increase in the skills of participants in completing OSN problems. In addition, participants can apply several mastery strategies for OSN material.